FORENISC FINDINGS IN EXHUMATIONS (Journal of Forensic Medicine & Toxicology, 2025)
OBJECT: To determine the forensic findings of Exhumation. DURATION AND PLACE: Study was conducted on Exhumed. Dead Bodies at different districts of Sindh. From January 2006 to December 2008. METHOD AND SUBJECT: Study was carried out on exhumed dead bodies of different Age, Sex and religion in different districts of Sindh. From January 2006 to December 2008. Total of (53) fifty three dead bodies were exhumed during the period, out of them 34 thirty four were males and nineteen 19 were females. RESULT: Total of fifty three dead bodies were exhumed, for forensic findings. Exhumation were carried out after two months to two years, in the presence of judicial body, on legal demand. Most of the dead bodies were in advance state of decomposition. Due to advance stage of decomposition, mark of violence at soft tissue, were lost. Organs were also in state of putrefaction, so histopathology did not gave too much about cause, of death.
Keywords: Exhumation; Grave; Exhumed Dead Bodies; Autoylysis, Facial Identification; Judicial Magistrate